2011
DOI: 10.1128/jcm.00091-11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of AmpC Beta-Lactamase in Escherichia coli: Comparison of Three Phenotypic Confirmation Assays and Genetic Analysis

Abstract: Two mechanisms account for AmpC activity in Escherichia coli, namely, mutations in the ampC promoter and attenuator regions resulting in ampC overexpression and acquisition of plasmid-carried ampC genes. In this study, we analyzed 51 clinical E. coli isolates with reduced susceptibility to amoxicillin-clavulanic acid, piperacillin-tazobactam, or extended-spectrum cephalosporins for the presence of AmpC production. Three phenotypic AmpC confirmation assays (cefoxitin-cloxacillin disk diffusion test, cefoxitin-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
124
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 38 publications
9
124
2
8
Order By: Relevance
“…Nucleotide sequencing of a representative group of these isolates (n = 7) revealed the bla CMY-2 gene. This observation is consistent with many other studies worldwide in which CMY-2 is the most commonly acquired plasmid and widely geographically distributed AmpC enzyme [5,[15][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nucleotide sequencing of a representative group of these isolates (n = 7) revealed the bla CMY-2 gene. This observation is consistent with many other studies worldwide in which CMY-2 is the most commonly acquired plasmid and widely geographically distributed AmpC enzyme [5,[15][16][17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies carried out in hospital laboratories and similar in design to this study have revealed various prevalence rates. For example, a study from Denmark reported a similar prevalence to our data, in which 17% (4/24) of E. coli carried a plasmid ampC gene [14], whilst a study in Switzerland reported a higher prevalence at 38% (8/21) [15]. The predominant ampC gene detected in this study was bla CIT , identified in 14 E. coli isolates.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, 6/26 (23.1%) PCR-positive isolates were carrying plasmid encoded AmpC β-lactamases of the family ACC rendering these strains appearing cefoxitin susceptible; as Peter-Getzlaff et al, (2011) stated that ACC-1 is inhibited by cefoxitin; so, FOX may appear susceptible.…”
Section: Screening For Ampc Production By Fox Disk Diffusion Methods (Dd)mentioning
confidence: 48%
“…Similarly, found that the sensitivity for CC-DD test for detection of AmpC was 97.2% and the specificity was 100% when using the same concentration and the same cutoff compared to both Modified three dimensional test and PCR. Also, Peter-Getzlaff et al, (2011) demonstrated that CC-DD test correctly detected 20/21 (95.2%) AmpC (chromosomal and plasmid-mediated) positive E. coli strains by PCR and did not give false-positive results when using the same concentration and the same cutoff. Ingram et al, (2011) demonstrated that the sensitivity and specificity of CC-DD test when using cloxacillin (100µg) were 53% and 99% respectively for detection of AmpC production.…”
Section: Cloxacillin Combined Disk Diffusion Test (Cc-dd)mentioning
confidence: 86%
See 1 more Smart Citation